MOTIVASI KERJASAMA EKSPOR LNG INDONESIA KE JEPANG 2008-2015 - Febrianto Fitra Utama; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study describe about Indonesian economic cooperation in the export of LNG to Japan in 2008-2015, which was written in a Joint Statement November 28, 2006.             The sources of this research were obtained through literature reviews, books, websites, and others. The source of analysis is qualitative methods. This study uses the level of analysis of the nation state, liberalism perspective considers that war is only a small part of existing reality. The liberalists hope international relation are understood throughly and not forget that cooperation between countries is one of the main things.             Indonesia is one of the biggest LNG producing countries, and Japan is an industrial country that needs energy to run its industry. This economic cooperation is a Japanese soft power strategy that has helped the Indonesian economy. See the condition of Japan that is in need of energy, one of which is LNG. Indonesia's LNG exports play a role in increasing the country's foreign exchange, with the existence of economic cooperation, especially in the energy sector, Japan as a partner also helps in the development of Indonesian LNG. Keywords: LNG, Energy, Export, Import, Economic Cooperation, IJEPA, Commodity.